Research on Satellite Internet Security Protection Based on Zero Trust - Yufei SONG; Wenhui ZHOU; Jiandong LIU; Xinpeng LI (天地一体化信息网络)
Satellite internet, as a new infrastructure, is an important part of China's future information infrastructure, and its security importance is self-evident.Based on the typical architecture of satellite internet system, the security risks faced by satellite platform control, satellite digital transmission and satellite communication were analyzed, the satellite internet security protection architecture based on zero trust was put forward.The implementation process of zero trust security protection architecture in satellite control, digital transmission and communication typical application scenarios, and its advantages compared with the traditional security protection architecture were described.